Driving social impact at the bottom of the Pyramid through the internet-of-things enabled frugal innovations. (December 2022) - Park, Sukyung; Rosca, Eugenia; Agarwal, Nivedita
Abstract: Emerging digital technologies create novel conditions for understanding fundamental societal developments. The academic debate has given little attention to understanding the impact of these digital transformations on key areas such as sustainable development. Hence, this study explores how frugal innovations in the healthcare and energy sector in Bottom of the Pyramid (BoP) markets drive social impact through the use of Internet-of-Things (IoT) technologies. This study focuses on understanding the underlying mechanisms through which technology enabled frugal innovations drive social impact in BoP markets. Using a multiple case analysis approach, the results suggest a distinction between technology providers and enablers as two different types of enterprises working towards developing and commercializing IoT technologies in BoP markets. The findings show that while providers tend to use knowledge on local constrains as inputs to design their activities to achieve local embeddedness, enablers incorporate local constrains in the early technology development process to design customized solutions for local community needs. Findings also highlight that IoT capabilities enable social outcome creation at individual, community and value chain levels. In particular, IoT capabilities moderate the transition from reactive to preventive intervention through their focus on sensing, dynamicity and real-time intelligence. Highlights: The study proposes two types of enterprises that are developing and commercializing IoT technologies in BoP markets. Providers create direct outcomes through their involvement in last mile delivery, enablers indirectly contribute to social impact. IoT capabilities enable social outcome creation at individual, community and value chain levels. IoT capabilities moderate the transition to preventive intervention through their focus on sensing and real-time intelligence.